2019
DOI: 10.1128/jvi.00612-19
|View full text |Cite
|
Sign up to set email alerts
|

Functional Correlation between Subcellular Localizations of Japanese Encephalitis Virus Capsid Protein and Virus Production

Abstract: The flavivirus capsid protein is considered to be essential for the formation of nucleocapsid complexes with viral genomic RNA at the viral replication organelle that appears on the endoplasmic reticulum (ER), as well as for incorporation into virus particles. However, this protein is also detected at the lipid droplet (LD) and nucleolus, and physiological roles of these off-site localizations are still unclear. In this study, we made a series of alanine substitution mutants of Japanese encephalitis virus (JEV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 45 publications
1
34
0
Order By: Relevance
“…These residues are highly conserved among the flaviviruses. The capsid protein has been shown to interact with LDs, and this interaction is crucial for virus replication and pathogenesis [18][19][20][21][22][23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These residues are highly conserved among the flaviviruses. The capsid protein has been shown to interact with LDs, and this interaction is crucial for virus replication and pathogenesis [18][19][20][21][22][23].…”
Section: Discussionmentioning
confidence: 99%
“…LDs have been described as platforms for HCV assembly, with the capsid localizing to the lipid droplets and subsequent recruitment of NS5A, which engages virus replication complexes to ld-associated membranes [18,19]. All the other flavivirus capsid proteins -DENV, Zika virus (ZIKV), West nile virus (WNV) and JEV -have been reported to localize on LDs and this association is crucial for virus particle formation [20][21][22][23]. Virions are assembled in close proximity to the ER and LDs and bud into the ER-lumen for envelopment followed by transport through the secretory pathway [24].…”
Section: Introductionmentioning
confidence: 99%
“…Although the molecular weight of flavivirus CPs is relatively low, they are actively transported into the nucleus but not by simple diffusion [44] , [46] . Interestingly, the nuclear localization signals (NLSs) of flavivirus CPs are heterogeneous [44] , [45] , [46] , [49] , [50] , [51] . It has also been demonstrated that the nuclear localization of flavivirus CPs is functionally correlated with virus production [45] , [49] , [51] .…”
Section: The Subcellular Distribution Of Capsid Proteinmentioning
confidence: 99%
“…Interestingly, the nuclear localization signals (NLSs) of flavivirus CPs are heterogeneous [44] , [45] , [46] , [49] , [50] , [51] . It has also been demonstrated that the nuclear localization of flavivirus CPs is functionally correlated with virus production [45] , [49] , [51] . It is worth stressing that the key sites of the predicted NLS are usually basic residues, which play a role in RNA binding for CPs.…”
Section: The Subcellular Distribution Of Capsid Proteinmentioning
confidence: 99%
“…Their ability to interact with lipid droplets is essential for efficient production of virus particles [14][15][16][17]. Capsid is also able to enter the nucleus and wreak havoc on ribosome biogenesis and the host transcriptome [18][19][20][21][22][23]. The function of these interactions within the nucleus and nucleolus in the context of the flavivirus life cycle is poorly understood.…”
Section: Introductionmentioning
confidence: 99%